x Turn on thread page Beta
 You are Here: Home >< Maths

# Prove: 1 + 1 = 2 watch

1. Prove:

1 + 1 = 2
2. I don't feel like it
3. (Original post by integral_neo)
Prove:

1 + 1 = 2
(Original post by integral_neo)

1 + 1 = 2
Proved.
4. (Original post by Pencil)
Proved.
Well done.
5. Attached Images

6. Doesnt it go back to euclidian rules of geometry, ie a thing of length one unit + a thing of length one unit = a thing of length 2 units, am i right???
7. (Original post by cobra01977)
Doesnt it go back to euclidian rules of geometry, ie a thing of length one unit + a thing of length one unit = a thing of length 2 units, am i right???
I thought you used Peano's axioms.
8. (Original post by Squishy)
I thought you used Peano's axioms.
Mine was a plain guess
9. My maths teacher had to do this at the beginning of her degree..
10. (Original post by imasillynarb)
My maths teacher had to do this at the beginning of her degree..
i know the proof is quite complex but I saw the newton proof for this but didnt understand it so i thought someone may know a method which i could understand
11. I did this in yr 10

let a = b

a² = ab Multiply both sides by a

a² + a² - 2ab = ab + a² - 2ab Add (a² - 2ab) to both sides

2(a² - ab) = a² - ab Factor the left, and collect like terms on the right

2 = 1 Divide both sides by (a² - ab)
12. (Original post by integral_neo)
i know the proof is quite complex but I saw the newton proof for this but didnt understand it so i thought someone may know a method which i could understand
2 + 2 = 4 we know this to be true
therefore, divide the whole lot by 2
1 + 1 = 2

Ruthie xx

i think i deserve a prize!
13. (Original post by Widowmaker)
I did this in yr 10

let a = b

a² = ab Multiply both sides by a

a² + a² - 2ab = ab + a² - 2ab Add (a² - 2ab) to both sides

2(a² - ab) = a² - ab Factor the left, and collect like terms on the right

2 = 1 Divide both sides by (a² - ab)
That wasn't the proof he wanted. He wanted 1 + 1 = 2, not 1 = 2.

I don't think you need to prove it, it's just definition.
14. (Original post by Widowmaker)
I did this in yr 10

let a = b

a² = ab Multiply both sides by a

a² + a² - 2ab = ab + a² - 2ab Add (a² - 2ab) to both sides

2(a² - ab) = a² - ab Factor the left, and collect like terms on the right

2 = 1 Divide both sides by (a² - ab)

2 = 1

who asked u to prove 2 = 1?
15. (Original post by ruthiepoothie)
2 + 2 = 4 we know this to be true
therefore, divide the whole lot by 2
1 + 1 = 2

Ruthie xx

i think i deserve a prize!

not correct
16. (Original post by Nylex)
That wasn't the proof he wanted. He wanted 1 + 1 = 2, not 1 = 2.

I don't think you need to prove it, it's just definition.

Proof does exist... and there are many versions of it
17. you cant prove an axiom!
18. (Original post by Willa)
you cant prove an axiom!
i have seen the proof for this in the principia by Newton, so yes u can and im sure an easier version of the proof exist
19. (Original post by JamesF)
Click

cheers

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: July 30, 2004
Today on TSR

Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams

## Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE